2017
DOI: 10.1080/00207454.2017.1374959
|View full text |Cite
|
Sign up to set email alerts
|

A study of oxidative stress in migraine with special reference to prophylactic therapy

Abstract: There is evidence of oxidative stress in migraine pathophysiology. Following treatment, oxidative stress declined following both pharmacological and rTMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 34 publications
6
54
0
1
Order By: Relevance
“…This link is supported by studies in which markers of increased oxi dative or nitrosative stress and/or decreased antioxidant capacity have been directly examined [54][55][56][57][58][59][60][61][62][63][64][65][66][67] (Supplementary Table 2). All studies of oxidative stress and/or antioxidant capacity in migraine have demonstrated that at least one marker is abnormal [54][55][56][57][58][59][60][61][62][63][64][65][66][67] . Of all biomarkers examined, superoxide dismutase activity seems to be the only one that is consistently reduced in patients with migraine, including interictally 68 .…”
Section: Oxidative and Nitrosative Stress And Antioxidant Capacitymentioning
confidence: 93%
See 1 more Smart Citation
“…This link is supported by studies in which markers of increased oxi dative or nitrosative stress and/or decreased antioxidant capacity have been directly examined [54][55][56][57][58][59][60][61][62][63][64][65][66][67] (Supplementary Table 2). All studies of oxidative stress and/or antioxidant capacity in migraine have demonstrated that at least one marker is abnormal [54][55][56][57][58][59][60][61][62][63][64][65][66][67] . Of all biomarkers examined, superoxide dismutase activity seems to be the only one that is consistently reduced in patients with migraine, including interictally 68 .…”
Section: Oxidative and Nitrosative Stress And Antioxidant Capacitymentioning
confidence: 93%
“…Other drugs used for prevention of migraine treat ment have clear metabolic effects. Amitriptyline also reduces markers of oxidative stress and increases anti oxidant capacity 65 . Valproate attenuates nitroglycerin induced trigeminovascular activation by preserving mitochondrial function in a rat model of migraine 211 and increases mitochondrial biogenesis 212 .…”
Section: Prophylactic Pharmaceuticalsmentioning
confidence: 99%
“…40 In non-mitochondrial migraine patients increased oxidative stress markers like malondialdehyde, total antioxidant activity, GSH/GSSG concentrations were observed as were decreased concentrations of plasma GSH, glutathionine-S-transferase (GST), and total antioxidant capacity compared to controls. 40,80 PET imaging with 56 Cu-ATSM and 18 FDG demonstrated increased oxidative stress and increased glucose metabolism following hyperemia in a MELAS syndrome patient with stroke-like episodes. 41 Importantly, to our best knowledge, so far none of these imaging studies have been done in migraine m.3243A>G patients without stroke-like episodes.…”
Section: Mitochondria: Structure Function and Pathologymentioning
confidence: 94%
“…Some studies have suggested that migraine may be the result of mitochondrial impairment, and therefore, since CoQ10 has been shown to improve mitochondrial oxidative phosphorylation in humans, it could be used as a successful migraine preventive to reduce the severity, length, and frequency of headaches (Rozen et al., ). In addition, there is an evidence of oxidative stress in migraine pathophysiology, which could explain the depletion of antioxidant levels in migraine patients when compared to controls (Tripathi, Kalita, & Misra, ). In fact, migraine patients have lower CoQ10 concentrations (Mason, ).…”
Section: Coq10 Supplementationmentioning
confidence: 99%